Asilomar survey: researcher perspectives on ethical principles and guidelines for BCI research. Issue 4 (2nd October 2018) - Pham, Michelle; Goering, Sara; Sample, Matthew; Huggins, Jane E.; Klein, Eran
ABSTRACT: Brain-computer Interface (BCI) research is rapidly expanding, and it engages domains of human experience that many find central to our current understanding of ourselves. Ethical principles or guidelines can provide researchers with tools to engage in ethical reflection and to address practical problems in research. Though researchers have called for clearer ethical principles or guidelines, there is little existing data on what form these should take. We developed a prospective set of ethical principles for BCI research with specific guidelines and shared them, via a survey, to participants at the 6th International BCI Meeting at the Asilomar Conference Center in 2016. Respondents were broadly supportive of principles of Care for Subjects, Modesty, Participation, Inclusivity, Relationality, Justice, and Social Impact. Principles more traditionally aligned with responsible conduct of research showed higher levels of endorsement. Researcher support for specific principle-based ethical guidelines varied with respect to stringency of researcher obligations.